(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article refers to the poetry of the Uzbek poetess Zulfiyakhonim, in whose work the image of a woman - a loving mother and a faithful woman - is studied. Also, the writer’s art of creating a poetic image is illuminated through the analysis of poems. The study of Zulfiyakhonim Israilova’s work shows that in the spirit and tone of such a creative work, in its meaning and direction, in the ideas and ideals expressed in it, the sad and passionate lament of a simple Uzbek woman is embodied. In this sense, the factor that ensured the warmth of Zulfiya’s work is her active humanism, poetic symbolism, and a world of attractive feelings. The article reflects precisely these aspects of the poet’s poetry.